2016
DOI: 10.1021/acs.energyfuels.6b01032
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Hydrodeoxygenation Activity of Carbon Supported Molybdenum Carbide and Oxycarbide Catalysts

Abstract: Carbothermal hydrogen reduction (CHR) of ammonium heptamolybdate impregnated activated charcoal (AC) yields a mixed Mo 2 C/MoO x C y catalyst. As the CHR temperature increases (from 600 to 800 °C) the Mo 2 C content increases. At 675 °C graphite networks are generated that attach to the β-Mo 2 C particles, and at ≥700 °C agglomeration and sintering occur, all of which decrease catalyst activity. An optimal CHR temperature of ∼650 °C is identified based on the catalyst activity for the hydrodeoxygenation (HDO) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
72
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(83 citation statements)
references
References 48 publications
10
72
1
Order By: Relevance
“…An alternative preparation method uses carbothermal hydrogen reduction (CHR), employing a carbon support and pure H2 to generate the metal carbide at high reduction temperatures (700-800 o C). This method yields nanoparticles of Mo2C, as first demonstrated by Mordenti et al [22] and Liang et al [23] and also reported previously by the authors [24]. Thus, CHR is a relatively facile method to synthesize carbon supported Mo2C catalysts, in which the carbon support may also suppress coke formation during residue oil upgrading [25].…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…An alternative preparation method uses carbothermal hydrogen reduction (CHR), employing a carbon support and pure H2 to generate the metal carbide at high reduction temperatures (700-800 o C). This method yields nanoparticles of Mo2C, as first demonstrated by Mordenti et al [22] and Liang et al [23] and also reported previously by the authors [24]. Thus, CHR is a relatively facile method to synthesize carbon supported Mo2C catalysts, in which the carbon support may also suppress coke formation during residue oil upgrading [25].…”
Section: Introductionsupporting
confidence: 68%
“…The calcined precursor (ca. 1.8 g) was placed in a U-tube reactor and subsequently converted to the Ni-Mo2C/AC catalyst by CHR in a continuous H2 flow (200 mL (STP)/min), while increasing temperature from room temperature to 500 o C at 10 o C /min, followed by increasing temperature at 1 o C/min to 650 o C and holding the final temperature for 90 min before quenching to room temperature in N2 [24]. This catalyst (designated as 10%Mo2C/AC-650) was compared with Ni-Mo2C/AC catalysts, prepared similarly but with successive impregnations of the AC with solutions of AHM and Ni(NO3)2, respectively, to obtain precursors with different Ni:Mo ratios.…”
Section: Catalyst Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The carbon loss of the catalyst increases from 14 to 50 and to 70 wt %a st he temperature increases from 600 to 700 and to 800 8C, respectively.T his is mainly caused by the formation of C x H y in the reduction gas (2xC + yH 2 !2C x H y )and the replacemento fOspecies in the Mo-based catalyst by C species. When the temperature rises to 700 8C, it is observed that most particles (4-6 nm) were inside the tubes (Figure 2e,f), although af ew particles were distributed outside the tubes and slightly aggregated (15)(16)(17)(18)(19)(20)(21)(22) nm, see Figure S1 ai nt he Supporting Information). As shown in Figure 2a,b,t he initial prepared particlesa re dispersed on the internal surfaces of the tubes for the AHM/CNTs.…”
Section: Controllable Synthesis Of Mo X C/cnt Catalystsmentioning
confidence: 97%
“…[19a, 20] All Mo-based catalysts were furthera nalyzed by TEM. The enlarged TEM images of these particles show a d-spacing of 0.228 nm assigned to the (1 01)p lane of the hexagonal phase of Mo 2 C, [20] as shown in Figure S2 (in the SupportingI nformation),p roving the particles both inside and outside the CNTsa re Mo 2 C. However,a ss hown in Figure 2g,h,t he formation of Mo 2 Ca nd destruction of the CNTst akep lace simultaneously at 800 8C. In the case of the Mo x C/CNTst reated at 600 8C, al arge number of particles with as ize range of 4-6 nm are uniformly distributed inside of CNTs ( Figure 2c,d).…”
Section: Controllable Synthesis Of Mo X C/cnt Catalystsmentioning
confidence: 99%